Krachtlijnen van een groen alternatief - De Clopper, Wim; Hendrickx, Vera; Stes, Jan; Malcorps, Johan (Brussel: Agalev, 1987)
"Agalev ; medewerkers : Wim De Clopper, Vera Hendrickx, Jan Stes,... et al. ; samenstelling en eindredaktie : Johan Malcorps"